Proceedings Seventh Asia-Pacific Software Engeering Conference. APSEC 2000
DOI: 10.1109/apsec.2000.896737
|View full text |Cite
|
Sign up to set email alerts
|

Platforms for agent-oriented software engineering

Abstract: Abstract

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Publication Types

Select...
3
2
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 14 publications
0
3
0
Order By: Relevance
“…For software agents, they are typically concerned with various aspects of multi-agent systems (MAS), including comparing agent platforms (Altmann et al, 2001;Nguyen et al, 2002;Laukkanen, 1999;Nowostawski et al, 2000;Ricordel and Demazeau, 2000), agent development kits (Bitting et al, 2003), mobile agent systems (Silva et al, 2001), or agent environments (Eiter and Mascardi, 2002). There are also comparisons of general agent systems and agent architectures per se (Sloman, 1998;Logan, 1998;Sloman and Scheutz, 2002).…”
Section: A Conceptual Framework For Comparing Rdesmentioning
confidence: 99%
“…For software agents, they are typically concerned with various aspects of multi-agent systems (MAS), including comparing agent platforms (Altmann et al, 2001;Nguyen et al, 2002;Laukkanen, 1999;Nowostawski et al, 2000;Ricordel and Demazeau, 2000), agent development kits (Bitting et al, 2003), mobile agent systems (Silva et al, 2001), or agent environments (Eiter and Mascardi, 2002). There are also comparisons of general agent systems and agent architectures per se (Sloman, 1998;Logan, 1998;Sloman and Scheutz, 2002).…”
Section: A Conceptual Framework For Comparing Rdesmentioning
confidence: 99%
“…Studies evaluating various MAS development toolkits (Shakshuki and Jun, 2004;Sánchez López et al, 2010) have shown that JADE can be used to build robust, complex and scalable MAS for most applications. Some reviews (Ricordel and Demazeau, 2000;Nowostawski et al, 2000) of agent development platforms suggest that the GUI of ZEUS, along with tools like report generation, statistical analysis and debugging make it a user friendly development environment for rapidly building scalable and distributable MAS, especially for beginners unfamiliar with the agent design paradigm. The same reviews also suggest that the ease of use may come at the cost of lost functionality.…”
Section: Discussionmentioning
confidence: 99%
“…Traditional software engineering development techniques based on functional analysis and data flow, or on object-oriented modeling, are in many cases not sufficient, in themselves, to capture needed dynamism and flexibility of some of the current development tasks that are undertaken [11] . Researchers are now seeking new methods and approaches that can help software engineers grapple with some of these problems.…”
Section: Introductionmentioning
confidence: 99%